2014
DOI: 10.1002/anie.201406491
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Generation of N‐Centered Hydrazonyl Radicals:  A Strategy for Hydroamination of β,γ‐Unsaturated Hydrazones

Abstract: A visible-light photocatalytic generation of N-centered hydrazonyl radicals has been accomplished for the first time. This approach allows efficient intramolecular addition of hydrazonyl radical to terminal alkenes, thus providing hydroamination and oxyamination products in good yields. Importantly, the protocol involves deprotonation of an N-H bond and photocatalytic oxidation to an N-centered radical, thus obviating the need to prepare photolabile amine precursors or the stoichiometric use of oxidizing reage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(135 citation statements)
references
References 70 publications
4
128
1
2
Order By: Relevance
“…Com- Scheme 5. The hydroamidation of benzamide derivatives reported by Chen. pared to those in their previous work, [17] the hydrazones can be substituted differently on the phenylsulfonyl ring (23). Aromatic and alkyl hydrazones were well tolerated, as shown in examples 20, 21, and 22.…”
Section: +supporting
confidence: 63%
See 2 more Smart Citations
“…Com- Scheme 5. The hydroamidation of benzamide derivatives reported by Chen. pared to those in their previous work, [17] the hydrazones can be substituted differently on the phenylsulfonyl ring (23). Aromatic and alkyl hydrazones were well tolerated, as shown in examples 20, 21, and 22.…”
Section: +supporting
confidence: 63%
“…[17] In their work, they were able to perform hydroamination reactions of sulfonohydrazone derivatives with pendant alkenes in an intramolecular fashion. Indeed, starting from readily synthesized sulfonohydrazone derivatives, they found that Ru(bpy) 3…”
Section: Nitrogen-centered Radical Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…47 The reaction of allyl hydrazone with TEMPO was performed in the presence of Ru(bpy) 3 Cl 2 and sodium hydroxide to afford cyclic products in 56-95% yields. The N-centered radical could be generated through oxidation of nitrogen anion which is generated by deprotonation of the hydrazone.…”
Section: Active Amidesmentioning
confidence: 99%
“…[5] Alkenes can also serve as redox compounds,and the resulting radical cations can be generated by removal of as ingle electron from an eutral parent compound. [5] Alkenes can also serve as redox compounds,and the resulting radical cations can be generated by removal of as ingle electron from an eutral parent compound.…”
mentioning
confidence: 99%